Strategies for analyzing tone languages - Coupe, Alexander R. (2015)
This paper outlines a method of auditory and acoustic analysis for determining the tonemes of a language starting from scratch, drawing on the author’s experience of recording and analyzing tone languages of north-east India. The methodology is applied to a preliminary analysis of tone in the Thang dialect of Khiamniungan, a virtually undocumented language of extreme eastern Nagaland and adjacent areas of the Sagaing Division Myanmar (Burma). Following a discussion of strategies for ensuring that data appropriate for tonal analysis will be recorded, the practical demonstration begins with a description of how tone categories can be established according to their syllable type in the preliminary auditory analysis. The paper then uses this data to describe a method of acoustic analysis that ultimately permits the representation of pitch shapes as a function of absolute mean duration. The analysis of grammatical tones, floating tones and tone sandhi are exemplified with Mongsen Ao data, and a description of a perception test demonstrates how this can be used to corroborate the auditory and acoustic analysis of a tone system.